Intravenous immunoglobulin treatment for secondary recurrent miscarriage: a randomised, double‐blind, placebo‐controlled trial. (21st November 2014) - Christiansen, OB; Larsen, EC; Egerup, P; Lunoee, L; Egestad, L; Nielsen, HS
<x xml:space="preserve">Abstract</x> Objective To determine whether infusions with intravenous immunoglobulin (IVIg) during early pregnancy increase live birth rate in women with secondary recurrent miscarriage compared with placebo. Design A single‐centre, randomised, double‐blind, placebo‐controlled trial. Setting A tertiary centre for recurrent miscarriage in Copenhagen, Denmark. Population A group of 82 women with unexplained secondary recurrent miscarriage and at least four miscarriages. Methods Women were randomly assigned to repeated infusions with IVIg or placebo (albumin) from the time of positive pregnancy test to gestational week 15 or pregnancy loss. Main outcome measure Primary outcome was birth with neonatal survival in all randomised women. Results In the intention‐to‐treat analyses, live birth rates were 23/42 (54.8%) in the IVIg and 20/40 (50.0%) in the placebo group, relative risk 1.11 (95% CI 0.70–1.74). In a per protocol analysis, almost identical results were found. The median gestational length at delivery was higher in the IVIg than the placebo group (282 versus 272 days, P = 0.02) but the mean birthweight was not significantly increased. Conclusions In this trial, which is the largest so far, IVIg did not increase the live birth rate in patients with secondary recurrent miscarriage and the treatment cannot be recommended in clinical practice.